B20 Dissecting the role of nucleolar stress in huntington's disease. (13th September 2016) - Parlato, Rosanna; Soenmez, Aynur; Spieth, Salome Tabea; Mustafa, Rasem; Litke, Christian; Kreiner, Grzegorz; Bierhoff, Holger; Tuorto, Francesca; Naranjo, Jose; Liss, Birgit
Abstract : Background: The expansion of CAG repeats in the mutant huntingtin (mHtt) protein impairs, among other fundamental cellular functions, the transcription of rRNA genes causing inhibition of rRNA synthesis and consequent disruption of nucleolar integrity, also known as nucleolar stress. Aims: We aim at dissecting the contribution of nucleolar stress to the onset and progression of HD. Methods/techniques: We mimicked for the first time nucleolar stress in striatal medium spiny neurons in mutant mice. This was achieved by conditional ablation of the nucleolar transcription factor TIF-IA gene, crucial for the recruitment of the RNA polymerase I to the rRNA promoters. Next we analysed behavioural, cellular and transcriptional changes in these mutants. Results/outcome: By this strategy we could specifically induce nucleolar stress-dependent signalling showing that it triggers pathophysiological and molecular similarities with HD. In particular we identified a neuroprotective response dependent on p53 activity, PTEN upregulation, mTOR downregulation and induction of autophagy at an early stage of nucleolar stress. Interestingly, we could find evidence of early compensatory mechanisms targeting nucleolar activity in HD cellular and mouse models. Moreover protein synthesis is altered by mHtt. Conclusions: These results allow not only to better understand mechanisms of HD but also to identify potential disease modifiers linked to altered nucleolar activity.